PENINGKATAN HASIL BELAJAR MELALUI MODEL PEMBELAJARAN DISCOVERY LEARNING BERBANTU VIDEO PEMBELAJARAN PADA PESERTA DIDIK KELAS V TEMA 8 DI SD NEGERI 2 TARUB TAHUN PELAJARAN 2020/2021 - Melisa Intan Sari; Choirul Huda; Joko Susanto (JURNAL HANDAYANI PGSD FIP UNIMED, 2021)
Abstract : Improving Learning Outcomes Through the Discovery Learning Learning Model Assisted by Video Learning for Class V Students Theme 8 at SD Negeri 2 Tarub for the 2020/2021 Academic Year. Teacher Professional Education Study Program, Postgraduate Faculty, PGRI University Semarang. Advisory Lecturer Choirul Huda M.Si, M.Pd. The Civil Service Teacher Joko S.Pd, M.Pd. The background that drives this research is the learning outcomes of fifth grade students at SD Negeri 2 Tarub on the Second Semester Daily Examinations who achieve the Minimum Completeness Criteria (KKM) only 4 of 14 students or 29%. This is because students often pay attention to other students so they are less focused in learning activities, students look passive, students are not active in asking or answering. The problem in this research is how to improve learning outcomes through the Discovery Learning learning model assisted by learning videos for Class V Theme 8 students at SD Negeri 2 Tarub for the 2020/2021 academic year. This study aims to find out how to improve learning outcomes through the Discovery Learning learning model assisted by video learning for students of Class V Theme 8 at SD Negeri 2 Tarub for the 2020/2021 academic year. This type of research is Classroom Action Research (CAR). The subject of this research is the learning outcomes of the students of Class V SD Negeri 2 Tarub, totaling 14 consisting of 5 male students and 9 female students. The object under study is the learning outcomes of students in thematic learning. The results of the research in the first cycle the average value of learning outcomes is 65.00 with an average percentage of learning completeness of 50%. In cycle II the average value of learning outcomes is 72.50 with an average percentage of learning completeness of 75%. Furthermore, in the third cycle the average value of learning outcomes is 81.43 with an average percentage of complete learning outcomes of 96.5%. That from cycle I to cycle II there was an increase in the average value of 7.5 with a percentage increase in mastery learning outcomes of 25%. Then the increase in the average value from cycle II to cycle III is 8.93 with an increase in the percentage of mastery learning outcomes of 21.5%. It can be seen that in cycle II and cycle III, the indicators of success have been achieved with the achievement of mastery learning outcomes, namely the second cycle of 75% and the third cycle of 96.5%. The conclusion is that the Discovery Learning learning model assisted by learning videos can improve the learning outcomes of students in class V Theme 8 at SD Negeri 2 Tarub for the 2020/2021 academic year.Keywords: CAR, discovery learning, learning outcomes Abstrak : Peningkatan Hasil Belajar Melalui Model Pembelajaran Discovery Learning Berbantu Video Pembelajaran Pada Peserta Didik Kelas V Tema 8 Di SD Negeri 2 Tarub Tahun Pelajaran 2020/2021. PTK. Program Studi Pendidikan Profesi Guru Fakultas Pasca Sarjana Universitas PGRI Semarang. Dosen Pembimbing Choirul Huda M.Si, M.Pd. Guru Pamong Joko S.Pd, M.Pd. Latar belakang yang mendorong penelitian ini adalah hasil belajar peserta didik kelas V di SD Negeri 2 Tarub pada Ulangan Harian Semester II yang mencapai Kriteria Ketuntutasan Minimal (KKM) hanya 4 dari 14 peserta didik atau 29%. Hal ini